2016
DOI: 10.1177/2319510x16671555
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of Corporate Social Responsibility and Firm Performance: Evidence from India

Abstract: Corporate social responsibility (CSR) has emerged as a crucial research domain over the last decade due to the imperative that when CSR activities are communicated in the form of a report, it helps in improving firm performance. Thus, the main purpose of the present study is to analyse CSR disclosure trend in India and to investigate the association between CSR and the performance of the firm from 2008-2009 to 2013-2014. Content analysis is employed using Global Reporting Initiative (GRI) framework as a base t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 61 publications
1
51
0
2
Order By: Relevance
“…Some researchers found CSR to be positively and significantly associated with firm value/performance, but a large number of studies revealed an insignificant association. The difference in results, as noted earlier, may be due to differences in methodology adopted, study period examined and the wide variation in variables used in measuring CSR, the different institutional setting, and to some extent the operational constructs [91], and importantly the problem of endogeneity [74]. According to Carrots and Sticks [92], there exists a positive theoretical relationship between CSR disclosure and firm value/performance.…”
Section: Prior Research On Csr Disclosure Performance and Firm Valuementioning
confidence: 99%
See 2 more Smart Citations
“…Some researchers found CSR to be positively and significantly associated with firm value/performance, but a large number of studies revealed an insignificant association. The difference in results, as noted earlier, may be due to differences in methodology adopted, study period examined and the wide variation in variables used in measuring CSR, the different institutional setting, and to some extent the operational constructs [91], and importantly the problem of endogeneity [74]. According to Carrots and Sticks [92], there exists a positive theoretical relationship between CSR disclosure and firm value/performance.…”
Section: Prior Research On Csr Disclosure Performance and Firm Valuementioning
confidence: 99%
“…All variables are listed and defined in Table 1 below. Consistent with prior disclosure research [91] that employed disclosure index, this study adopts the disclosure formula below to construct the three separate disclosure performance indexes.…”
Section: Measurement Of Variables and Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many research studies were conducted in Nigeria, and in other parts of the world in the quest for inding the relevance of CSR to corporate performance, divergent results were however documented. While the work of Adeneye and Ahmed (2015) Al-Samman and Al-Nashmi (2016), Akanbi and Ofoegbu (2012), Laskar and Maji (2016), Yusoff and Adamu (2016), inds the existence of positive impact of CSR on all the irms performance, Babalola (2012), Islam, Ahmed, and Hasan (2012); inds no signi icant impact between CSR and corporate performance. These divergent results are perceived to stem from the different methodologies, in terms of measures of CSR and corporate performance, adopted by the researchers involved, and this keeps the debate a loat.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In this study, I reviewed various research conducted by different scholars. Laskar and Maji (2017) conducted research on disclosure of corporate social responsibility (CSR) and financial performance: evidence from India. The result showed a positive impact of CSR on all the firms' performance.…”
Section: Review Of Literaturementioning
confidence: 99%